The proximal point algorithm with a general perturbation on geodesic spaces - Takuto Kajimura; Yasunori Kimura (Results in Applied Mathematics, 2025)
In this paper, we show some properties of a proximal mapping with a general perturbation for convex functions. We further investigate the existence and approximation of minimizers of a given convex function by using the proximal point algorithm with a general perturbation in complete geodesic spaces.